The other Fab Four the remarkable true story of the Liverbirds, Britain's first female rock band ; [a memoir] - McGlory, Mary; Saunders, Sylvia (Grand Central Publishing, 2024)
"The idea for Britain's first female rock band, The Liverbirds, started one evening in 1962, when Mary McGlory, then age 16, saw The Beatles play live at The Cavern Club in Liverpool, the nightclub famously known as the "cradle of British pop music." Then and there, she decided she was going to be just like them--and be the first girl to do it. Joining ranks in 1963 with three other working-class girls from Liverpool--drummer Sylvia Saunders and guitarists Valerie Gell and Pamela Birch, also self-taught musicians determined to "break the male monopoly of the beat world"--The Liverbirds went on to tour alongside the Rolling Stones, the Kinks, and Chuck Berry, and were on track to hit international stardom--until life intervened, and the group was forced to disband just five years after forming in 1968. Now, Mary and Sylvia, the band's two surviving members, are ready to tell their stories. From that fateful night in 1962, when Mary, who once aspired to become a nun, decided to provide for her family by becoming a rich-and-famous rocker, to the circumstances that led to the band splitting up--Sylvia's dangerously complicated pregnancy, and the tragic accident that paralyzed Valerie's beau-- The Liverbirds tackles family, friendship, addiction, aging, and the forces--even destiny--that initially brought the four women together." --
"A memoir" auf dem Cover
Keywords: The Liverbirds; Liverbirds (Musical group); Women rock musicians / England; Rock musicians / England / Biography; Rock music / England / 1961-1970; Musiciennes rock / Angleterre; Rock (Musique) / Angleterre / 1961-1970; Musiciens rock / Angleterre / Biographies; Biographies